ChemInform Abstract: Nickel‐Catalyzed Decarboxylative C—P Cross‐Coupling of Alkenyl Acids with P(O)H Compounds. Issue 10 (March 2015) - Wu, Yile; Liu, Liu; Yan, Kaili; Xu, Pengxiang; Gao, Yuxing; Zhao, Yufen
Abstract Conditions A) are found to be optimal for the preparation of a large variety of phosphorus compounds bearing an (E)‐1‐alkenyl part.